Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2020)
A dataset containing 432159 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is one of (Eleocharis geniculata (L.) Roem. & Schult., Leucothoe axillaris (Lam.) D.Don, Phoradendron leucarpum (Raf.) Reveal & M.C.Johnst., Solidago speciosa Nutt., Vitis labrusca L., Rubus cuneifolius Pursh, Prunus serotina Ehrh., Symphoricarpos orbiculatus Moench, Adlumia fungosa (Aiton) Greene ex Britton, Stern & Poggenb., Physalis lanceolata Michx., Trianthema portulacastrum L., Lycopodiella inundata (L.) Holub, Schizachyrium scoparium (Michx.) Nash, Drymaria cordata (L.) Willd. ex Schult., Ophioglossum petiolatum Hook., Symplocos tinctoria (L.) L'Hér., Dendrolycopodium obscurum (L.) A.Haines, Polygonatum biflorum (Walter) Elliott, Oxalis corniculata L., Menyanthes trifoliata L.)", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 432159 records from 1096 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0025906-200613084148143/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences